Machine translation of Indonesian: a review - Septarina, Amalia Agung; Rahutomo, Faisal; Sarosa, Moechammad (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2019)
Today, Machine Translation have an important role in communication. The need of Machine Translation System is getting higher in this information era. Some Machine Translation already exist, but many researcher interested to improve the quality of translation more natural. Find an optimal translation is not an easy thing to do in language processing. In this paper, we discuss about Machine Translation survey that contain Indonesia language to other language. There are different approaches to machine translation. Various method used in evaluating were also discussed like BLEU and NIST. Moreover, its future works to improve the translation quality. From the review results obtained that the translation has better performance depend on the number of corpus, well-behaved aligned corpus, and the technique used.